Sociocultural practices in maternal health among women in a less developed economy: An overview of Sokoto State, Nigeria - Muazu Alhaji Shamaki,; Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
This study explores sociocultural and traditional practices associated with maternal health in Sokoto state, Nigeria. These practices play significant roles in the life of women folks in the zone. Past researches show that Nigeria is culturally diverse with over 300 different ethnic or linguistic groups and dialects. In this study, sources of data and information include field observations, current literature in international journals, other academic researches, government publications, United Nation reports, USAID resources, and Pathfinder International materials. The findings reveal that tradition-inspired practices and norms such as unattended labour and delivery, low level of education, hot-bath (Wankan jego) during new birth, use of herbs, forced marriage, early marriage, child spacing, female genital mutilation and traditional gender discrimination play a significant role in maternal health, and are believed to account for the high maternal mortality rates in the state. Although such practices are predominant among women with low education attainment their general influence remains strong even in the face of extensive modernisation such that they need to be addressed more squarely if maternal mortality is to be reduced. Hence, the study recommends that instead of investing in the provision of more modern health facilities that are grossly underutilised commensurate effort should be made in tackling traditional beliefs and practices among women in the state.